(untitled) (Journal of the College of Basic Education, 2022)
The aims of the reseach is to nkow the using of the ElictronicEduction program to learn these skill of shotting the Ball to the Bascketforword and to learn passing . Quickly in Basket Ball . The reascher prove that learing those Skills by watching those skill in Tv after contact the Tv with (LAP TOP) is usefull to learn those skill than to learnt with out it .